2021
DOI: 10.3390/ijerph18179044
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Limited Health Literacy and Its Associated Factors among Elderly Patients Attending an Urban Academic Primary Care Clinic in Malaysia

Abstract: Limited health literacy (HL) is linked to many negative health outcomes, including poor self-management of chronic diseases and medication adherence among patients. There are a lack of data regarding HL in the elderly population in Malaysia. This study aimed to determine the prevalence of limited HL levels and its associated factors among elderly patients in an urban academic primary care clinic in Selangor, Malaysia. A cross-sectional study was conducted among 413 elderly patients (≥60 years old) who attended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
3
0
2
Order By: Relevance
“…Based on the characteristics of the population in these studies, the percentages of inadequate, low, or limited HL levels varied between 3.5% (among 4589 cancer patients in China) 24 and 84.5% (among 1360 community residents aged 15-69 years in Shanghai). 37 The most common determinants associated with their HL level were age, 13,15,16,24,36,15,40,41,44,45,53 -70 education, 13,16,24,30,32,15,35 -37,39,40,44,45,50,52 -58,60 -66,68,71 …”
Section: Resultsmentioning
confidence: 99%
“…Based on the characteristics of the population in these studies, the percentages of inadequate, low, or limited HL levels varied between 3.5% (among 4589 cancer patients in China) 24 and 84.5% (among 1360 community residents aged 15-69 years in Shanghai). 37 The most common determinants associated with their HL level were age, 13,15,16,24,36,15,40,41,44,45,53 -70 education, 13,16,24,30,32,15,35 -37,39,40,44,45,50,52 -58,60 -66,68,71 …”
Section: Resultsmentioning
confidence: 99%
“…In our study, the domain of ‘disease management’ had the lowest median knowledge score, similar to Goldsworthy et al [10], This lack of knowledge by patients on clinical management may be due to the ‘one-way style’ of communication between doctors and patients in Asia, with little room for input or queries from patients [32,33]. In addition, the health literacy of our patients may have been poor as the median age of our patients was 65 years, and published literature has indicated that younger patients were more likely to seek information digitally than older patients [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, a larger sample size was required when health literacy was considered. Abd-Rahim et al 40 reported a mean proportion of those who have adequate health literacy as 80% (334/413). Using sample size for proportion, with a total population of 5500 CKD patients in clinic CKD register, the minimum required sample is 229, with 95% confidence interval and 5% precision.…”
Section: Methodsmentioning
confidence: 99%